INDIRECTNESS OF EXPRESSION IN A COLLECTION OF GEGURITAN BY USTADJI PANTJA WIBIARSA - Cindy Permata Sari; Setyowati, Herlina; Qurniawati, Zuly (Department Javanese Literature and Language Education in Collaboration with Faculty of Teacher Training and Education Muhammadiyah University of Purworejo, 2025)
The aim of this research is to describe the indirectness of expression from the collection of geguritan (Javanese poetry) by Ustadji Pantja Wibiarsa, describe a heuristic and hermeneutic reading of the collection of geguritan by Ustadji Pantja Wibiarsa. This type of research is qualitative in the field of literary studies. Data from this research was collected using library techniques, listening techniques and note-taking techniques. The primary data from this research is in the form of words or sentences contained in each geguritan by Ustadji Pantja Wibiarsa, which consists of 37 geguritan titles. Secondary data from this research are books and articles that support this research. Data analysis this research is content analysis. The results of the analysis show that there are indirect expressions of geguritan, including: 1) meaning replacement, which consists of 11 data of simile, 315 data of metaphor, 20 data of personification, 3 data of metonymy, and 5 data of synecdoche, 2) meaning deviation, which consisting of 1 data of ambiguity, 5 data of contradiction, and 6 data of nonsense, 3) meaning creation, which consists of 191 data of enjambment, 24 data of homologues, and 37 data of typography. As for the hermenutical meaning, various meanings were found which were conveyed implicitly, consisting of, efforts to achieve ideals, disobedience, love of the country, life problems, abandoned children, heroes, greed, peace, gratitude, people. old, culture, crime, hostility, peace, and religion.